Sublingual Atropine Administration as a Tool to Decrease Salivary Glands' PSMA-Ligand Uptake: A Preclinical Proof of Concept Study Using [68Ga]Ga-PSMA-11 - Vincent Nail; Béatrice Louis; Anaïs Moyon; Adrien Chabert; Laure Balasse; Samantha Fernandez; Guillaume Hache; Philippe Garrigue; David Taïeb; Benjamin Guillet (MDPI AG, 2022)
Prostate Specific Membrane Antigen (PSMA)-directed radionuclide therapy has gained an important role in the management of advanced castration-resistant prostate cancer. Although extremely promising, the prolongation in survival and amelioration of disease-related symptoms must be balanced against the direct toxicities of the treatment. Xerostomia is amongst the most common and debilitating of these, particularly when using an alpha emitter. It is therefore of main importance to develop new preventive strategies. This preclinical study has evaluated the effect of α-adrenergic and anticholinergic drugs on [99mTc]TcO4− Single Photon Emission Computed Tomography/Computed Tomography (SPECT/CT) and [68Ga]Ga-PSMA-11 Positron Emission Tomography (PET/CT). Methods: The effects of phenylephrine, scopolamine, atropine, and ipratropium on salivary glands uptake were evaluated in non-tumor-bearing mice by [99mTc]TcO4− microSPECT/CT. The most efficient identified strategy was evaluated in non-tumor-bearing and xenografted mice by [68Ga]Ga-PSMA-11 PET/CT. Results: Scopolamine and atropine showed a significant decrease in the parotid glands' uptake on SPECT/CT whereas phenylephrine and ipratropium failed. Atropine premedication (sublingual route), which was the most effective strategy, also showed a drastic decrease of [68Ga]Ga-PSMA-11 salivary glands' uptake in both non-tumor-bearing mice (−51.6% for the parotids, p < 0.0001) and human prostate adenocarcinoma xenografted mice (−26.8% for the parotids, p < 0.0001). Conclusion: Premedication with a local administration of atropine could represent a simple, safe, and efficient approach for reducing salivary glands' uptake.